2018
DOI: 10.1038/s41380-018-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

The novel ghrelin receptor inverse agonist PF-5190457 administered with alcohol: preclinical safety experiments and a phase 1b human laboratory study

Abstract: Rodent studies indicate that ghrelin receptor blockade reduces alcohol consumption. However, no ghrelin receptor blockers have been administered to heavy drinking individuals. Therefore, we evaluated the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD) and behavioral effects of a novel ghrelin receptor inverse agonist, PF-5190457, when co-administered with alcohol. We tested the effects of PF-5190457 combined with alcohol on locomotor activity, loss-of-righting reflex (a measure of sedative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 66 publications
0
83
0
Order By: Relevance
“…Recent human work with the GHS‐R1a inverse agonist PF‐5190457 highlights the clinical relevance of the presented data. Although preliminary, this recent Phase 1b human laboratory study indicated that PF‐5190457 is safe to administer to individuals with alcohol use disorder, and also that PF‐5190457 reduced cue‐induced alcohol and food cravings …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent human work with the GHS‐R1a inverse agonist PF‐5190457 highlights the clinical relevance of the presented data. Although preliminary, this recent Phase 1b human laboratory study indicated that PF‐5190457 is safe to administer to individuals with alcohol use disorder, and also that PF‐5190457 reduced cue‐induced alcohol and food cravings …”
Section: Discussionmentioning
confidence: 93%
“…administration of exogenous ghrelin significantly potentiated alcohol cue‐induced craving in a bar‐like laboratory in individuals with AUD . Preliminary evidence with a similar population indicates that oral administration of a selective GHS‐R1a inverse agonist, PF‐5190457, reduces craving in a bar‐like laboratory in a small Phase 1b placebo‐controlled human laboratory study . In addition, i.v.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, GHSR activity can affect alcohol‐induced reward and compulsive alcohol intake in rodents, independently of circulating ghrelin levels . Notably, a recent preliminary study reported that administration of the GHSR inverse agonist PF‐5190457 reduces alcohol and food craving in humans . Therefore, pharmacological manipulation of ligand‐independent GHSR activity appears to comprise a promising strategy for treating not only binge eating, but also a variety of other pathological consummatory behaviours with important clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the role of the ghrelin receptor constitutive activity reported in this work should be taken into account when considering its inverse agonists as anti-obesity agents (57), or their use for the treatment of alcohol use disorder (35,36). The novel object recognition task was adapted from Leger and colleagues (41), the object displacement test was adapted from Oliveira and colleagues (42) and the elevated plus maze was performed according to (58) .…”
Section: Discussionmentioning
confidence: 99%
“…Here, using a combination of imaging, biochemical and electrophysiological approaches, and behavior analysis, we uncover a role for the constitutive activity of the ghrelin receptor in providing tonic control for the regulation of AMPA receptor traffic, influencing synaptic plasticity in the hippocampus and interfering with learning and memory in vivo. These finding should be taken into account given that inverse agonists of the ghrelin receptor are presently being tested in humans to treat alcohol use disorder (35,36).…”
Section: Introductionmentioning
confidence: 99%